2008
DOI: 10.4319/lo.2008.53.6.2451
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Cu and Fe availability on the growth and Cu:C ratios of marine diatoms

Abstract: We investigated the effects of copper (Cu) and iron (Fe) availability on the growth rates, cellular Cu content, and steady-state Cu uptake rates of eight species of centric diatoms (coastal and oceanic strains). Whereas Fe and Cu availability had a significant effect on the growth rates of both costal and oceanic diatoms, an interaction between Fe and Cu availability and growth rates was only observed for the oceanic diatoms. Determination of cellular Cu : carbon (C) quotas using the radiotracers 67 Cu and 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
116
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 42 publications
21
116
1
Order By: Relevance
“…This Cu-limiting threshold is significantly higher than some denitrifying bacteria (, 10 216 mol L 21 ) that-like N. maritimuspossess copper metalloenzymes essential to their energy production and denitrifying activity . The N. maritimus Cu-limiting threshold is also higher than that of the coastal diatoms Chaetoceros decipiens and Thalassiosira weissflogii and the coccolithophore Emiliania huxleyi, which grow at 77%, 76%, and 88%, respectively, of their m max at [Cu 2+ ] , 10 215 mol L 21 (Sunda and Huntsman 1995;Annett et al 2008). In contrast, the oceanic diatom T. oceanica, achieves 65% of its m max at [Cu 2+ ] , 10 213.9 mol L 21 (Peers et al 2005), a value that is similar to N. maritimus.…”
Section: Discussionmentioning
confidence: 99%
“…This Cu-limiting threshold is significantly higher than some denitrifying bacteria (, 10 216 mol L 21 ) that-like N. maritimuspossess copper metalloenzymes essential to their energy production and denitrifying activity . The N. maritimus Cu-limiting threshold is also higher than that of the coastal diatoms Chaetoceros decipiens and Thalassiosira weissflogii and the coccolithophore Emiliania huxleyi, which grow at 77%, 76%, and 88%, respectively, of their m max at [Cu 2+ ] , 10 215 mol L 21 (Sunda and Huntsman 1995;Annett et al 2008). In contrast, the oceanic diatom T. oceanica, achieves 65% of its m max at [Cu 2+ ] , 10 213.9 mol L 21 (Peers et al 2005), a value that is similar to N. maritimus.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that Cu starvation induced different physiological modifications from Fe limitations (i.e., that for P. delicatissima, most of cellular Cu is probably used for physiological mechanisms other than Fe transport). Annett et al (2008) also demonstrated that for six out of eight strains of diatoms (and five out of six species), Cu demand of the high-affinity Fe transport system is low relative to other cellular Cu pools. The discriminant analysis also suggests that during co-limitations, even though Cu had an effect by itself, Fe limitation triggered the main response.…”
Section: Discussionmentioning
confidence: 99%
“…It was later proved that Cu limitation indeed decreased Fe uptake rates and that transcription levels of a putative multi-copper oxidase gene were significantly elevated in Fe-limited cells of Thalassiosira pseudonana (Peers et al 2005;Maldonado et al 2006). More recent studies, however, demonstrated that, for some diatoms, the Cu demand of the high-affinity Fe transport system may be low relative to other cellular Cu pools, such as Cu-containing SOD and cytochrome c oxidase (Annett et al 2008). For example, although the oceanic diatom Thalassiosira oceanica needs Cu to acquire Fe (Peers et al 2005), most of the Cu requirement of this species is attributable to its use of the Cu-containing plastocyanin rather than Fe-rich cytochrome c 6 in the photosynthetic apparatus (Peers and Price 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later work showed the existence of an efflux system for Cu from the Cu stressed cells of the cyanobacteria Synechococcus (Croot et al, 2003). Recent works on the uptake of Cu by phytoplankton have utilized the longer lived isotope 67 Cu to obtain important information on the uptake kinetics of Cu by diatoms (Guo et al, 2010), determined cellular Cu quotas for different phytoplankton types (Quigg et al, 2006) and showed the dependence of Cu on Fe uptake (Maldonado et al, 2006) and in turn the role of Fe in determining the cellular quota for Cu (Annett et al, 2008). However the most exciting application so far has been the first reported use of 67 Cu for work performed using natural phytoplankton assemblages from the North Pacific (Semeniuk et al, 2009).…”
Section: Copper (Cu)mentioning
confidence: 99%